Effect of Agility on the Ability to Dribble in Football Games For Extracurricular Students at SMP Negeri 3 Sirah Pulau Padang - Sutrisno, Sutrisno; Rahman, Andi; Handayani, Widya (Journal of Social Work and Science Education, 2023)
The purpose of this study was to determine the effect of agility to ability dribbling in the game of football for students in extracurricular SMP Negeri 3 Sirah Pulau Padang. The exploratory research method used was a one-group design experiment before and after the test. With a one group pre and post-test design. The population in this research was students who participated in football extracurricular activities, the sample in this research was 32 people. The research instrument used was the soccer dribbling test. The treatment in this study took the form of agility training, which was carried out for 6 weeks with a training frequency of 3 times a week. The performance test uses the experimental method with the results of the characteristic “t test” α = 0.05, obtained t count = (3.85) while t table = (2.037), so Ha is accepted while H0 is rejected. According to the results of the study that Ha is acceptable, then agility training affects ability enhancement soccer dribbling the ball.